A comparative histological study of the vegetative parts of mangroves Hilairanthus germinans (Acanthaceae), Laguncularia racemosa, Conocarpus erectus (Combretaceae), Rhizophora mangle and R. racemosa (Rhizophoraceae) (Revista Científica Ciencias Naturales y Ambientales, 2021)
Mangroves are complex ecosystems that occur in flooded, hypoxic, and saline environments with poorly consolidated soils, the dominant vegetation commonly known as mangroves have developed morphological and physiological characteristics that allow them to survive in those ecosystems. The present work was based on the characterization of vegetative tissues of mangrove trees as Hilairanthus germinans, Laguncularia racemosa, Conocarpus erectus, Rhizophora mangle and R. racemosa, describing their histological differences. For this purpose, leaves were collected, transported, and kept cold until processing. The cuts were made manually, FAA (formol, acetic acid and alcohol), methylene blue, and liquid glycerin were used for fixation and assembly. Posteriorly, those were observed in optical light microscopes, the tissues were measured with micrometric strips. All species analyzed showed a thick cuticle and abundant spongy tissue, and vessels. H. germinans presented a large amount of pyriform trichomes both in leaves and petioles. A great quantity of aerenchyma was observed in roots except for Rhizophora, in the latter genus the sclerenchymatous tissue was abundant.
Keywords: Aerenchyma; Mangrove; Plant histology; Pneumatophores